O009 Keep The Chin Up: Evidence-based standardised care pathway for infants with Pierre Robin Sequence (PRS). (9th November 2022) - Goel, D; Wilson, A; O'Donnell, A; Rao, S; Herbert, H; Pachter, N; Hamden, B; Gillett, D
Abstract: Background: Management of upper airway obstruction in neonates with Pierre Robin Sequence (PRS) is challenging given difficulties in grading severity of disease, difficulties obtaining early polysomnography (PSG) and variable practices with no widely accepted standard protocol. We aimed to develop a standardised care pathway for infants with PRS. Methods: Total 190 publications were identified of which 21 were reviewed in detail. Majority were review articles or retrospective studies. Consultation was obtained from the Complex Airway Team (multidisciplinary team of neonatologist, paediatric sleep specialist, otolaryngologist, plastic surgeon, clinical nurse specialist and speech pathologist), geneticists, audiologists, the consumer group "PRS Australia" and ANZ paediatric sleep physicians. Final recommendations were based on consensus and quality of the evidence. Results: We developed a pathway outlining sequential interventions to manage OSA based on functional assessment by PSG (7-14 day of life) and structural assessment by flexible nasal endoscopy "FNE" (0-7 day of life). Conduct of bedside PSG in NICU instead of sleep lab enables innovative, timely, patient-centred and cost-effective service delivery. We standardised reporting of glossoptosis (Yellon classification), laryngomalacia (Olney et.al) and airway (Seattle DISE scoring) on FNE. Early multidisciplinary involvement, structured assessment of feeding, synchronous airway lesions and associated genetic syndromes is also considered. The pathway allows for standardised management and discharge planning with clearly defined multidisciplinary follow-ups. Intended outcome/impact: This project is likely first in Australia to standardise care pathway for infants with PRS encompassing collaborative, innovative and structured care delivery principles. The project provides foundation for future clinical and research collaboration.